(untitled) (Archives of Criminology, 1993)
A study of two 100-person groups of juvenile delinquents born in 1959 was conducted in the years 1981‒1985 at the Department of Criminology, Institute of Legal Studies, Polish Academy of Sciences. The first (experimental) group consisted of boys randomly selected from the total of 225 juveniles born in 1959 who had committed at least on offence while intoxicated. The other (control) group were 100 randomly juveniles selected from the entire population of 8196 juvenile delinquents born in 1959. None of the juveniles selected for the experimental group happened to find themselves in the control group as well. As shown by the findings, the juveniles who had committed at least one offence while intoxicated were much more demoralized as a group than the whole of juvenile delinquents. It seemed interesting, therefore, to follow the further fates of both groups as adults. The follow-up period was 7 years; until that time, all of the examined persons reached the age of 25 when the average Polish man be- comes stabilized to some extent, having graduated from university, worked for several or a dozen years (upon completion of secondary or elementary education respectively), and frequently having also established a family. Data on the life situation of the young men from both examined groups on their 25th birthday were obtained from the following four sources: ‒ the Central Register of Convicted Persons kept by the Ministry of Justice, and the Register of Convicted and Detained Persons where criminal records of the entire sample were checked; ‒ files of criminal cases of all men with criminal records (47.0% of the experimental and 35.0% of the control group); the files concerned criminal proceedings before common courts for offences committed after coming of age; ‒ questionnaire survey of 63.0% of the experimental and 66.0% of the control group; ‒ inquiry submitted to the sobering-up stations concerning the entire sample. As shown by the findings, 24.0% of the experimental and 13.0% of the control group established their own families before the age of 25. The proportions are high, as regards the experimental group in particular: erly in the 1980s, the newly married constituted about 10% of the total male population aged 20‒24 in Poland. The mean educational level was higher in the control compared to the experimental group; this concerns first and foremost cases of education higher than the elmementary technical (of which there were two in the experimental compared to ten in the control group). Moreover, no cases of illiteracy could be found in the control group, compared to one such case in the experimental group. Of all the men of the experimental group concerning whom data could be obtained, 80.4% had a regular job, and 19.6% stayed out of job or worked casually. Of the control group, 80.0% had a regular job (33% combining job with school), 18.3% stayed out of job or worked casually, and one person had entered university. The number of convicted persons in the experimental group (47) was larger compared to the control group (35) by 12.0%, the difference being significant. Also relapse into crime was higher in the expenmental group (l5 vs. 11 cases). The first offence committed by those convicted as young adults was mainly one against property: 35 cases in the experimental group (66.0% of all those convicted) and 28 cases in the control group (80.0%). The second most frequent offence of members of the experimental group was an aggressive act: against life and health, freedom, personal dignity and inviolability (10 persons, i.e. 18.8% of all those convicted). The offences of this type included: bodily injury (Art. 156 of the penal code – 3 persons, i.e. 6.4%); participation in a brawl or beating (Art. 158 and 159 – 1 person, i.e. 2.1%); infringement of bodily inviolability (Art. 182 – 3 persons, i.e. 6.4%); assault against a public functionary (Art. 233 and 234 – 1 person, i.e. 2.1%); insult against a public functionary (Art. 236 – 1 person, i.e. 2.1%). In the control group, 6 cases of such offences could be found (9.1% of all those convicted); yet the only offence under Art. 148 1 of the penal code, that is homicide, had been committed by a member of that goup.The other discussed figures and proportions were respectively: Art. l58, 159 – 3 persons, i.e. 8.6%; Art. 182 – 1 person (2.9%); Art. 233, 234 – 1 person (2.9%); and Art. 236 – 1 person (29%). Beside offences, the two groups manifested also other synptoms of social maladjustment. The symptoms found most often in both groups were: “contacts with persons known to the police as delinquent” and stays at the sobering-up station. As regards the experimental group, the third frequent symptom were brawls in the place of residence followed by bad opinion with neighbors, hooliganism, and avoidance of work. In the control group, avoidance of work ranked third, followed by bad opinion with neighbors, hooliganism, and brawls at the place of residence. This ranking of frequency of the symptoms of social maladjustment points to a greater aggressiveness of the young men from the experimental group. On the 63 young men from the experimental group concerning whom data could be obtained, 62 (98.0%) drank alcohol. In the control group 59 (89.0%) of the 66 concerning whom data could be obtained were drinkers. The group of drinkers included all those who had drunk several times a week already as juveniles, and 70% of those who had drunk once a week. In the control group, drinkers included 91.7% of those who had drunk as juvoniles (11 of 12 cases). Of those who had drunk as juveniles in the control group, 66.7% (8 cases) were convicted as adults. As shown by the discussed data, young men from the experimental group – those who committed as juveniles at least one offence while intoxicated prove much inferior in terms of the social situation to other men who also committed offences as juveniles but did not drink alcohol. Therefore, early alcohol consumption among juvenile delinquents is an important factor of a negative prognosis as to the further fates of such persons. A number of postulates have been formulated, addressed at the prosecuting agencies, criminal justice, and institutions designed to assist persons in extraordinary situation. With respect to the present sample, all such postulates acquire special importance and must be met without fail.